Theoretical premises on the potentialities of the culture as a tool for local development actors (Original) (REDEL. Revista Granmense de Desarrollo Local, 2019)
In the present article elementary concepts are defined, which respond to the need of determining the theoretical premises of cultural potentialities as a tool of the actors for local development. It is structured first,on the conceptual aspects of local development and its dimensions, secondly the cultural potentialities and their identification in local development as a tool for local actors and third, an analysis of the theoretical premises of local actors is carried out.
Keywords: local development, social actors, culture, local culture